Study of the Nerve Injury in Parotid Gland Surgery - Rahman, MA; Alam, MM; Joarder, AH (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.1 Issue 1 (Jan-Jun 2011) 17-19 DOI: http://dx.doi.org/10.3126/njenthns.v2i1.6779